Computers in Business - Sanders, Donald H; Grolier business library (New York McGraw-Hill, Inc., 1990)
The book is meant to introduce both the future users and data processing beginners at an early stage in their college programs to many of the important topics that are likely to be relevant to them in their future career
Includes bibliographical and index.
gp. 13/06/2019
Loans